Novel molecular biomarkers of cancer therapy‐induced cardiotoxicity in adult population: a scoping review - Irene Cartas‐Espinel; Marcelino Telechea‐Fernández; Carlos Manterola Delgado; Andrés Ávila Barrera; Nicolás Saavedra Cuevas; Angela L. Riffo‐Campos (ESC Heart Failure, 2022)
Abstract Aim Cancer treatments are associated with cardiotoxic events that predispose to cardiac pathology and compromise the survival of patients, making necessary the identification of new molecular biomarkers to detect cardiotoxicity. This scoping review aims to identify the available evidence on novel molecular biomarkers associated with cardiotoxicity in the adult population undergoing cancer therapy. Methods and results The databases Medline, Web of Science, Scopus, and Embase were screened for the identification of published studies until 23 August 2020, searching for novel molecular biomarkers reported in cancer therapy‐related cardiac dysfunction in adult patients. A total of 42 studies that met the eligibility criteria were included. Fourteen studies reported 44 new protein biomarkers, 18 studies reported 57 new single nucleotide polymorphism biomarkers, and 11 studies reported 171 new gene expression profiles associated with cardiotoxicity. Data were extracted for 272 novel molecular biomarkers reported and evaluated in 7084 cancer patients, of which only 13 were identified in more than one study (MPO, sST2, GDF‐15, TGF‐B1, rs1056892, rs1883112, rs4673, rs13058338, rs1695, miR‐1, miR‐25‐3p, miR‐34a‐5p, and miR‐423‐5p), showing values for area under the curve > 0.73 (range 0.74–0.85), odds ratio 0.26–7.17, and hazard ratio 1.28–1.80. Conclusions Multiple studies presented a significant number of novel molecular biomarkers as promising predictors for risk assessment of cardiac dysfunction related to cancer therapy, but the characteristics of the studies carried out and the determinations applied do not allow suggesting the clinical use of these molecular biomarkers in the assessment of cancer therapy‐induced cardiotoxicity.